Optimizing Energy Storage for Efficient Microgrid Operation by Mountaineering Team-Based Approach - Shayeghi, Hossein; Davoudkhani, Iraj Faraji; Nabatalizadeh, Javad; Bizon, Nicu (2024 International Congress on Human-Computer Interaction, Optimization and Robotic Applications (HORA), 2024)
The storage of electrical energy in power systems has always been a subject of interest. Despite significant advancements in the field of electrical energy storage, it still faces numerous challenges on a large scale. The primary challenge in the initial stages of utilizing electrical energy storage devices is determining the appropriate capacity and location for installation, considering both technical constraints and economic limitations. Therefore, in this article, the simultaneous determination of the capacity and location of two different technologies of energy storage devices and the optimal charging and discharging scheduling of these systems in a microgrid is proposed as an optimization problem. Additionally, the impact of demand response (DR) participation in selecting the optimal energy storage system (ESS) and installation location is analyzed and investigated. To solve this problem, a mountaineering team-based optimization (MTBO) algorithm is employed. The proposed method is implemented and evaluated on a real-world microgrid comprising various energy resources. The simulation results demonstrate the effectiveness of the proposed approach in optimal placement and capacity determination of energy storage in the microgrid.